The Peace Message of Islam Rahmatan Lil Alamin: A Pathway to Resolving Conflict and Genocide in Palestine through Political Exegesis - Basid, Abdul; Nasih, Ahmad Munjin; Hanafi, Yusuf; Kholidah, Lilik Nur; Ahmed, Bakri Mohamed Bkheet (AJIS: Academic Journal of Islamic Studies, 2024)
This research discusses human rights violations committed by Israel against Palestinians, especially in the crime of genocide that is currently shocking the world. The purpose and benefits of this research are to provide facts about the Palestinian-Israeli conflict so that it can build sympathy and care for people who are facing conflict and need help. Furthermore, secondary data sourced from textual such as various research, books, discussion videos, reading materials, and other academic publications on the theme of the Palestinian-Israeli conflict are used to collect data and information for this academic study. The formulation of the issues discussed is the violation of human rights of the Israeli Genocide against Palestine, the Transcription and comments of the Indonesian people, the Tafsir and Asbabun Nuzul QS Al-Hujurat verse 13, and the contribution of the peace verse in overcoming conflict and genocide in Palestine. Surah Al-Hujurat contains messages of peace, brotherhood, and rejecting behaviour that degrades or discredits others. Thus, while there are claims of genocide committed by Israel against Palestinians, Surah Al-Hujurat in Islam contains messages of peace and brotherhood that are relevant to the conflict situation.